Correction: Madden et al. A Systems Thinking Approach Investigating the Estimated Environmental and Economic Benefits and Limitations of Industrial Hemp Cultivation in Ireland from 2017–2021. Sustainability 2022, 14, 4159 - Madden, Sinéad M.; Ryan, Alan; Walsh, Patrick (Sustainability, 2022)
The authors would like to make the following corrections to the published paper [...]